Associations between Human leukocyte antigen, PTPN22, CTLA4 genotypes and rheumatoid arthritis phenotypes of autoantibody status, age at diagnosis and erosions in a large cohort study. Issue 3 (31st July 2007) - Karlson, E W; Chibnik, L B; Cui, J; Plenge, R M; Glass, R J; Maher, N E; Parker, A; Roubenoff, R; Izmailova, E; Coblyn, J S; Weinblatt, M E; Shadick, N A
Abstract : Background: HLA-DRB1 shared epitope ( HLA-SE ), PTPN22 and CTLA4 alleles are associated with cyclic citrullinated peptide (CCP) and rheumatoid arthritis (RA). Objective: We examined associations between HLA-SE, PTPN22, CTLA4 genotypes and RA phenotypes in a large cohort to (a) replicate prior associations with CCP status, and (b) determine associations with radiographic erosions and age of diagnosis. Methods: A total of 689 RA patients from the Brigham RA Sequential Study (BRASS) were genotyped for HLA-SE, PTPN22 (rs2476601) and CTLA4 (rs3087243). Association between genotypes and CCP, rheumatoid factor (RF) erosive phenotypes and age at diagnosis were assessed with multivariable models adjusting for age, sex and disease duration. Novel causal pathway analysis was used to test the hypothesis that genetic risk factors and CCP are in the causal pathway for predicting erosions. Results: In multivariable analysis, presence of any HLA-SE was strongly associated with CCP+ (odds ratio (OR) 3.05, 95% CI 2.18–4.25), and RF+ (OR 2.53, 95% CI 1.83–3.5) phenotypes; presence of any PTPN22 T allele was associated with CCP+ (OR 1.81, 95% CI 1.24–2.66) and RF+ phenotypes (OR 1.84, 95% CI 1.27–2.66). CTLA4 was not associated with CCP or RF phenotypes. While HLA-SE was associated with erosive RA phenotype (OR 1.52, 95% CI 1.01–2.17), this was no longer significant after conditioning on CCP. PTPN22 and CTLA4 were not associated with erosive phenotype. Presence of any HLA-SE was associated with an average 3.6 years earlier diagnosis compared with absence of HLA-SE (41.3 vs 44.9 years, p = 0.002) and PTPN22 was associated with a 4.2 years earlier age of diagnosis (39.5 vs 43.6 years, p = 0.002). CTLA4 genotypes were not associated with age at diagnosis of RA. Conclusions: In this large clinical cohort, we replicated the association between HLA-SE and PTPN22, but not CTLA4 with CCP+ and RF+ phenotypes. We also found evidence for associations between HLA-SE, and PTPN22 and earlier age at diagnosis. Since HLA-SE is associated with erosive phenotype in unconditional analysis, but is not significant after conditioning on CCP, this suggests that CCP is in the causal pathway for predicting erosive phenotype.